Postoperative stereotactic radiosurgery for resected brain metastases: A comparison of outcomes for large resection cavities - Zhong, Jim (Pract Radiat Oncol, 2017)
PURPOSE: Although historical trials have established the role of surgical resection followed by whole brain irradiation (WBRT) for brain metastases, WBRT has recently been shown to cause significant neurocognitive decline. Many practitioners have employed postoperative stereotactic radiosurgery (SRS) to tumor resection cavities to increase local control without causing significant neurocognitive sequelae. However, studies analyzing outcomes of large brain metastases treated with resection and postoperative SRS are lacking. Here we compare outcomes in patients with large brain metastases >4 cm to those with smaller metastases ≤4 cm treated with surgical resection followed by SRS to the resection cavity. METHODS AND MATERIALS: Consecutive patients with brain metastases treated at our institution with surgical resection and postoperative SRS were retrospectively reviewed. Patients were stratified into ≤4 cm and >4 cm cohorts based on preoperative maximal tumor dimension. Cumulative incidence of local failure, radiation necrosis, and death were analyzed for the 2 cohorts using a competing-risk model, defined as the time from SRS treatment date to the measured event, death, or last follow-up. RESULTS: A total of 117 consecutive cases were identified. Of these patients, 90 (77%) had preoperative tumors ≤4 cm, and 27 (23%) >4 cm in greatest dimension. The only significant baseline difference between the 2 groups was a higher proportion of patients who underwent gross total resection in the ≤4 cm compared with the >4 cm cohort, 76% versus 48%, respectively (P <.01). The 1-year rates of local failure, radiation necrosis, and overall survival for the ≤4 cm and >4 cm cohorts were 12.3% and 16.0%, 26.9% and 28.4%, and 80.6% and 67.6%, respectively (all P >.05). The rates of local failure and radiation necrosis were not statistically different on multivariable analysis based on tumor size. CONCLUSIONS: Brain metastases >4 cm in largest dimension managed by resection and radiosurgery to the tumor cavity have promising local control rates without a significant increase in radiation necrosis on our retrospective review.